Do radiological and functional outcomes correlate for fractures of the distal radius?. (March 2017) - Plant, C. E.; Parsons, N. R.; Costa, M. L.
Abstract : Aims: We conducted a study to determine whether radiological parameters correlate with patient reported functional outcome, health-related quality of life and physical measures of function in patients with a fracture of the distal radius. Patients and Methods: The post-operative palmar tilt and ulnar variance at six weeks and 12 months were correlated with the Patient Rated Wrist Evaluation, Disabilities of the Arm, Shoulder and Hand, and EuroQol scores, grip strength, pinch strength and range of movement at three, six and 12 months for 50 patients (mean age 57 years; 26 to 85) having surgical fixation, with either percutaneous pinning or reconstruction with a volar plate, for a fracture of the distal radius. Results: Radiological parameters were found to correlate poorly with the patient reported outcomes (r = 0.00 to 0.47) and physical measures of function (r = 0.01 to 0.51) at all intervals. Conclusion: This study raises concerns about the use of radiological parameters to determine management, and to act as a surrogates for successful treatment, in patients with a fracture of the distal radius. Restoration of 'normal' radiographic parameters may not be necessary to achieve a satisfactory functional outcome for the patient. Cite this article: Bone Joint J 2017;99-B:376–82.